Pengaruh Hasil Belajar Mata Kuliah Vokal Terhadap Hasil Belajar Mata Kuliah Paduan Suara Di Prodi Pendidikan Sendratasik Konsentrasi Musik Jurusan Sendratasik FBS UNP - Ghina Lenggo Geni; Jagar Lumbantoruan (SENDRATASIK UNP, 2021)
This study aims to determine the magnitude of the effect of vocal course learning outcomes on choir course learning outcomes of students (2017 generation) in Music Concentration, Sendratasik Education Study Program, Department of Sendratasik, FBS UNP. This is a quantitative research using a correlational method. The population in this study was students (2017 generation) in Sendratasik Education Study Program, Music Concentration Department of Sendratasik, FBS UNP. The sample in the study was the learning outcomes of students of Sendratasik Education Study Program, Music Concentration, Department of Sendratasik, FBS, UNP in vocal and choir courses. This research used primary and secondary data sources. The data analysis was conducted by using product moment correlation technique. The results of research and data processing as well as testing the hypothesis show that the correlation coefficient (r) obtained in the learning outcomes of vocal courses and learning outcomes of choir courses from three classes of 65 people from the 2017 generation of Sendratasik Education Study Program is 0.16127 or 16.127% and it is categorized very weak. In class A, the value obtained is 0.453 or 45.3% and it is categorized quite influential. In class B, the value obtained is 0.1605 or 16.05% and it is categorized very low. In class C, the value obtained is -0,1297 or -12.97%. This predicate gives no effect. The total percentage is 45.3% + 16.05% -12.97% = 16.127%. Thus, the analysis of student learning outcomes is 1: 2.